ELITE TRADISIONAL DALAM PERGUMULAN SISTEM RELIGIO POLITICAL POWER - Joebagio, Hermanu (History Department, Semarang State University and Historian Society of Indonesia, 2012)
This study was aimed to describe: (1) the relation among political groups in the system of religio political power, (2) the political system when dealing with foreign trade organization (VOC), and also (3) the political system encouraging vertical mobility of the Javanese society. This research employed historical methods, and the data were collected from both primary and secondary sources. Meanwhile, the reconstruction of historiography greatly regarded diachronic and synchronic aspects. The results of this study showed that religio political power was produced by the process of Islamization. In that political system, there was equality of position between the rulers and the ulama. The ulama as a representation of the people, bring about the consequence that all public policy must be approved by them. Political system is equal to Ã¢â‚¬Ëœdescending of powerÃ¢â‚¬â„¢. This political system underwent a political change when the central government moved to rural Java, that is changed into nomadism and schizophrenia, because of the strong subordination and repression to the ulama and the opposition groups. The political violence would not build vertical mobility of Javanese people both in education and economic development. Furthermore, this system would face difficulty when deling with the strategy of ex-nihilo by VOC. Key words: religio political power, Islamization, the ulama, ex-nihilo, vertical mobilityÃ‚Â Studi ini bertujuan untuk mendeskripsikan: (1) relasi antar kelompok politik dalam sistem religio political power, (2) sistem politik itu ketika berhadapan dengan organisasi dagang asing, dan (3) sistem politik itu memacu mobilitas vertikal masyarakat Jawa. Riset ini menggunakan adalah metode sejarah, dan pengumpulan data melalui sumber primer dan sekunder. Sementara itu rekonstruksi sejarah utamakan segi diakronik dan sinkronik. Hasil penelitian menunjukkan bahwa sistem religio political power adalah hasil dari proses Islamisasi. Dalam sistem politik itu terdapat kesejajaran kedudukan antara penguasa dan ulama. Ulama sebagai representasi rakyat memiliki konsekuensi setiap kebijakan publik perlu mendapat persetujuan ulama. Sistem politik mempunyai bentuk yang sama dengan descending of power. Sistem politik ini mengalami perubahan ketika pusat pemerintahan berpindah di pedalaman Jawa, yakni menjadi nomadisme dan schizophrenia, karena kuatnya represi terhadap ulama dan kelompok oposisi. Kekerasan politik itu tidak akan membangun mobilitas vertikal masyarakat Jawa, baik bidang pendidikan maupun pembangunan ekonomi. Bahkan akan menghadapi kesulitan ketika berhadapan dengan strategi ex-nihilo VOC. Kata kunci: religio political power, Islamisasi, ulama, ex-nihilo, dan mobilitas vertikal Ã‚Â Ã‚Â